PENGARUH METODE ROLE PLAYING PADA TEMA BINATANG TERHADAP SIKAP KEDISIPLINAN ANAK USIA 5-6 TAHUN DI TK NURUNNAJAH - Nur Hasanah; Evita Anggereini; Sri Indriani Harianja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Role-playing is a game in which children imitate or portray people, plants, animals, or events. Discipline is the attitude whereby a person adheres to the rules of their environment, whether written or unwritten. In this learning activity, role-playing is implemented to enhance children’s disciplinary attitudes, provide explanations, and facilitate learning that can develop various aspects of children’s potential. The objective of this study is to determine the effect of role-playing on the “animals” theme on the disciplinary attitudes of 5- to 6-year-old children at Nurunnajah Kindergarten. The research question in this study is: how does the use of the role-playing method on the theme of animals affect the disciplinary attitudes of 5- to 6-year-old children at Nurunnajah Kindergarten? This study is a quantitative study using an experimental method. The study population consists of 40 children, and the sample consists of 19 children. The data collection method used in this study was observation. The data analysis methods used in this study included the t-test, normality test, homogeneity test, and hypothesis testing. Based on the analysis of the pre-test and post-test results, a calculated t-value of 9.46188 was obtained. When compared to the critical t-value of 2.110, the calculated t-value is greater than the critical t-value. This indicates that the role-playing method on the animal theme has an effect on the disciplinary attitudes of 5- to 6-year-old children at Nurunnajah Kindergarten. The conclusion of this study is that the role-playing method on the theme of animals has an effect on the disciplinary attitudes of 5- to 6-year-old children at Nurunnajah Kindergarten, as evidenced by the calculated t-value (9.46188) being greater than the critical t-value (2.110).